To investigate kadiorespiratorny system of students in norm and at a patolgiya of a thyroid gland. (Experimental biology, 2016)
The study of the heart of the students in health and disease of the thyroid gland is an important problem at the present time. In recent years for the study of daily physiological condition of the heart, and ECG are used Microvit MT-101 Holter recorder MT-200 and analysis software that allows for recording the physiological function of the heart for a long time (e.g. at intervals between 24 and 72 hours). It was found that in normal and pathological conditions of the thyroid gland. and indicators of heart rate change in students. The results show the influence of thyroid pathology in the cardiorespiratory system of students. These data can be used to monitor the health and quality of life of students.
Keywords: heart; cardiovascular system; thyroid; hormone tireiodny; cardiorespiratory; registrar Halter; heart rate.